Monoclonal Antibodies for Non-Hodgkin's Lymphoma: State of the Art and Perspectives - Giulia Motta; Michele Cea; Eva Moran; Federico Carbone; Valeria Augusti; Franco Patrone; Alessio Nencioni (Clinical and Developmental Immunology)
Monoclonal antibodies have been the most successful therapeutics ever brought to cancer treatment by immune technologies. The use of monoclonal antibodies in B-cell Non-Hodgkin's lymphomas (NHL) represents the greatest example of these advances, as the introduction of the anti-CD20 antibody rituximab has had a dramatic impact on how we treat this group of diseases today. Despite this success, several questions about how to optimize the use of monoclonal antibodies in NHL remain open. The best administration schedules, as well as the optimal duration of rituximab treatment, have yet to be determined. A deeper knowledge of the mechanisms underlying resistance to rituximab is also necessary in order to improve the activity of this and of similar therapeutics. Finally, new antibodies and biological agents are entering the scene and their advantages over rituximab will have to be assessed. We will discuss these issues and present an overview of the most significant clinical studies with monoclonal antibodies for NHL treatment carried out to date.